The development and validation of the extended active-passive social media use scale - Xiang Niu; Philippe Verduyn; James Gaskin; Sebastian Scherr; Dean McDonnell; Jin-Liang Wang (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2025)
Mixed findings regarding the relationship between social media (SM) use and mental health have left the research field at somewhat of a crossroads, with one significant requirement being a comprehensive tool to measure SM use. In an effort to advance relevant research, this study extends the common ‘active-passive model’ of SM use to develop and validate a comprehensive scale. This scale will measure complex SM behaviors, focusing on subtypes of active and passive use. A 29-item Extended Active-Passive Use Scale (E-APUS) developed for adolescents and young adults was validated using a total sample of individuals (N = 4,372) from four independent Chinese samples. An exploratory factor analysis with N1 = 305 and a confirmatory factor analysis with N2 = 289 revealed six dimensions characterizing engagement on SM. These dimensions include targeted-warm use, non-targeted-warm use, cold use, browsing high self-relevance success stories, browsing low self-relevance success stories, and browsing failure stories. The study confirmed measurement invariance (N3 = 3,524) across genders and educational stage groups (i.e., adolescents vs. young adults) through (multi-group) confirmatory factor analyses. Convergent validity of the E-APUS scale was established with active-passive SM use measures, and criterion validity was supported using indicators of subjective well-being. However, discriminant validity was comparatively lower for personality factors. The E-APUS scale exhibited good internal consistency and high test-retest reliability (N4 = 254) over a 2-week period. Summarily, the E-APUS emerges as an effective, valid, and reliable tool for measuring SM use.